Comparative effect of Piper betle, Chlorella vulgaris and tocotrienol-rich fraction on antioxidant enzymes activity in cellular ageing of human diploid fibroblasts - Makpol, Suzana (BioMed Central, 2013)
BACKGROUND: Human diploid fibroblasts (HDFs) undergo a limited number of cellular divisions in culture and progressively reach a state of irreversible growth arrest, a process termed cellular ageing. Even though beneficial effects of Piper betle, Chlorella vulgaris and tocotrienol-rich fraction (TRF) have been reported, ongoing studies in relation to ageing is of interest to determine possible protective effects that may reverse the effect of ageing. The aim of this study was to evaluate the effect of P. betle, C. vulgaris and TRF in preventing cellular ageing of HDFs by determining the activity of antioxidant enzymes viz.; catalase, superoxide dismutase (SOD) and glutathione peroxidase. METHODS: Different passages of HDFs were treated with P. betle, C. vulgaris and TRF for 24 h prior to enzymes activity determination. Senescence-associated beta-galactosidase (SA β-gal) expression was assayed to validate cellular ageing. RESULTS: In cellular ageing of HDFs, catalase and glutathione peroxidase activities were reduced, but SOD activity was heightened during pre-senescence. P. betle exhibited the strongest antioxidant activity by reducing SA β-gal expression, catalase activities in all age groups, and SOD activity. TRF exhibited a strong antioxidant activity by reducing SA β-gal expression, and SOD activity in senescent HDFs. C. vulgaris extract managed to reduce SOD activity in senescent HDFs. CONCLUSION: P. betle, C. vulgaris, and TRF have the potential as anti-ageing entities which compensated the role of antioxidant enzymes in cellular ageing of HDFs.